Microalgae as a Feedstock for Sustainable Fatty Acids: Factorial Design Study - Molgero Da Ros, Patricia Caroline; Menezes, Talitha Kuhn; Bredda, Eduardo Henrique [UNESP]; Silva, Messias Borges [UNESP]; De Castro, Heizir Ferreira (Wiley-Blackwell, 2019)
Microalgal oil from Nannochloropsis gaditana cultivated in a laboratory-scale photobioreactor was submitted to enzymatic hydrolysis using Candida rugosa lipase. A 2(2) full factorial design was performed to evaluate the effects of the soy lecithin emulsifier concentration and the lipase loading on the formation of free fatty acids. As control, a similar set of reactions was carried out with macaw palm oil. The results showed similar hydrolysis yields for both feedstocks. The highest value was reached when the concentrations of soy lecithin and lipase were taken at their lowest and highest levels, respectively. The hydrolysate from microalgal oil showed that the majority of the fatty acids released by C. rugosa consisted of palmitic, oleic, and linoleic acids.
Keywords: Enzymatic hydrolysis; Lipases; Microalgal oils; Nannochloropsis gaditana; Polyunsaturated fatty acids